Ethical challenges causing moral distress: nursing home staff’s experiences of working during the COVID-19 pandemic - Annaclara Ariander; Anna Olaison; Christer Andersson; Rune Sjödahl; Lena Nilsson; Lisa Kastbom (Scandinavian Journal of Primary Health Care, 2024)
AbstractObjective To investigate the experiences of healthcare staff in nursing homes during the COVID-19 pandemic.Design Individual interviews. Latent qualitative content analysis.Setting Ten nursing homes in Sweden.Subjects Physicians, nurses and nurse assistants working in Swedish nursing homes.Main outcome measures Participants’ experiences of working in nursing homes during the COVID-19 pandemic.Results Four manifest categories were found, namely: Balancing restrictions and allocation of scarce resources with care needs; Prioritizing and acting against moral values in advance care planning; Distrust in cooperation and Leadership and staff turnover – a factor for moral distress. The latent theme Experiences of handling ethical challenges caused by the COVID-19 pandemic gave a deeper meaning to the categories.Conclusion During the pandemic, nursing home staff encountered ethical challenges that caused moral distress. Moral distress stemmed from not being given adequate conditions to perform their work properly, and thus not being able to give the residents adequate care. Another aspect of moral distress originated from feeling forced to act against their moral values when a course of action was considered to cause discomfort or harm to a resident. Alerting employers and policymakers to the harm and inequality experienced by staff and the difficulty in delivering appropriate care is essential. Making proposals for improvements and developing guidelines together with staff to recognize their role and to develop better guidance for good care is vital in order to support and sustain the nursing home workforce.